Transcriptome-Guided Mining of Genes Involved in Crocin Biosynthesis - Ji, Aijia; Jia, Jing; Xu, Zhichao; Li, Ying; Bi, Wu; Ren, Fengming; He, Chunnian; Liu, Jie; Hu, Kaizhi; Song, Jingyuan (Frontiers in Plant Science, 2017)
Gardenia jasminoides is used in traditional Chinese medicine and has drawn attention as a rich source of crocin, a compound with reported activity against various cancers, depression and cardiovascular disease. However, genetic information on the crocin biosynthetic pathway of G. jasminoides is scarce. In this study, we performed a transcriptome analysis of the leaves, green fruits and red fruits of G. jasminoides to identify and predict the genes that encode key enzymes responsible for crocin production, compared with Crocus sativus. Twenty-seven putative pathway genes were specifically expressed in the fruits, consistent with the distribution of crocin in G. jasminoides. Twenty-four of these genes were reported for the first time, and a novel CCD4a gene was predictedthat encodes carotenoid cleavage dioxygenaseleading to crocin synthesis, in contrast to CCD2 of Crocus sativus. In addition, 6 other candidate genes (ALDH12, ALDH14, UGT94U1, UGT86D1, UGT71H4 and UGT85K18) were predicted to be involved in crocin biosynthesis following phylogenetic analysis and different gene expression profiles. Identifying the genes that encode key enzymes should help elucidate the crocin biosynthesis pathway.